High expression levels of putative hepatic stem/progenitor cell biomarkers related to tumour angiogenesis and poor prognosis of hepatocellular carcinoma. Issue 7 (4th May 2010) - Yang, Xin-Rong; Xu, Yang; Yu, Bin; Zhou, Jian; Qiu, Shuang-Jian; Shi, Guo-Ming; Zhang, Bo-Heng; Wu, Wei-Zhong; Shi, Ying-Hong; Wu, Bin; Yang, Guo-Huan; Ji, Yuan; et al.
Abstract : Background/aims: To investigate the prognostic values of putative hepatic stem/progenitor cell (HSC/HPC) biomarkers in patients with hepatocellular carcinoma (HCC). Methods: Fourteen biomarkers related to HSCs/HPCs or tumour angiogenesis were assessed by qRT-PCR and then validated by tissue microarrays (TMAs) in three independent cohorts of patients with HCC undergoing curative resection (n=67, 314 and 73). Results: Most of the biomarkers were found to be overexpressed in patients with recurrent HCC by quantitative reverse transcription–PCR (qRT–PCR). The HSC/HPC biomarkers cytokeratin 19, ATP-binding cassette subfamily G member 2 (ABCG2), CD133, Nestin and CD44, and the markers of angiogenesis microvessel density (MVD, determined by CD34 immunostaining), vascular endothelial growth factor (VEGF) and platelet-derived endothelial cell growth factor (PD-ECGF) were confirmed as significant predictors for overall survival (OS) and/or relapse-free survival (RFS) in TMA analysis. As compared with the low HSC/HPC profile group, patients with a high HSC/HPC profile who had higher VEGF levels (p=0.012) and MVD (p=0.030) in tumours had significantly lower OS and RFS (p<0.0001). Based on Cox regression, a simplified model including CD133, CD44, Nestin and MVD was constructed and confirmed as an independent predictor for OS (p<0.0001) and RFS (p<0.0001), regardless of α-fetoprotein level, tumour stage and recurrence time (p<0.0001 for all). Conclusion: High expression levels of HSC/HPC biomarkers are related to tumour angiogenesis and poor prognosis of HCC. The simplified model based on the HSC/HPC and tumour angiogenesis profile can be used to classify patients with HCC with a high risk of tumour recurrence after surgery.